129k views
2 votes
Factor each polynomial x2-36

2 Answers

5 votes

I only see the polynomial
x^2-36, so I'll factor that one.

We can use two approaches: the most "standard" one requires us to find the roots of the polynomial. Then, for each root
x_i we write the factor
(x-x_i), and decompose the polynomials like this:


x^2-36=0 \iff x^2 = 36 \iff x = \pm√(36) = \pm 6

So, the root
6 yields the factor
(x-6), and the root
-6 yields the factor
(x+6). This means that the polynomial can be factored as


x^2-36 = (x+6)(x-6)

Alternatively, you can observe that the polynomial comes in the form
a^2-b^2, and it can be factored as


a^2-b^2 = (a-b)(a+b)

which again leads to


x^2-36 = (x)^2 - (6)^2 = (x+6)(x-6)

User Arrayfire
by
5.6k points
3 votes
(x+6)(x-6) would be the factored form
User Castrohenge
by
5.9k points